Rancang Bangun Kapal Tanpa Awak Guna Mendeteksi Navigation Lamp Untuk Menghindari Tubrukan - Akhmad Rizqi Aprilianto; Sri Mulyanto H; Siti Fatimah; Henna Nurdiansari; Akhmad Kasan Gupron (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The Unmanned ships have become a primary focus in maritime technology development to enhance efficiency and navigational safety in waters. In this research, a unmanned ship utilizing ESP32CAM as its core system is designed to detect navigation lights of other vessels and avoid potential collisions. The initial response of the ESP32CAM camera reads the colors of lights approaching the unmanned ship within a distance of less than 100cm. The ESP32CAM reads and identifies colors through image processing. When the ESP32CAM detects green and red lights, it commands the buzzer to sound. The color detection system works such that when the ESP32CAM detects a red light, it sends a signal to the servo motor to move left, and when it detects a green light, it sends a signal to the servo motor to move right. The servo motor functions as the ship's rudder. Testing of the navigation light system with ESP32CAM camera to prevent ship collisions is conducted with predetermined scenarios, including testing with red LEDs, green LEDs, and overall system testing. The results show that the navigation light system with ESP32CAM camera functions well. The ESP32CAM camera can optimally identify light colors at a distance of 100cm. Based on the conducted research, the ESP32CAM camera is capable of reading both the distance and colors of lights as specified at a distance of 100cm.